2020
DOI: 10.2147/ott.s260993
|View full text |Cite
|
Sign up to set email alerts
|

<p>Coexistence of Low-Grade Fetal Adenocarcinoma and Adenocarcinoma in situ of the Lung Harboring Different Genetic Mutations: A Case Report and Review of Literature</p>

Abstract: Low-grade fetal lung adenocarcinoma (L-FLAC) is an exceptionally rare pulmonary tumor, presenting with unclear histological and molecular features. In particular, the potential driver genes of L-FLAC remain elusive. To date, only five reports have documented genetic aberrations in L-FLAC. In the current study, we describe an unusual case of L-FLAC coexisting with adenocarcinoma in situ (AIS) of the lung, harboring different genetic mutations. A 39-year-old non-smoker female patient was referred to our hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
0
11
2
Order By: Relevance
“…After a careful review, 12 articles with featured molecular findings 4 , 7 9 , 18 , 22 25 and/or detailed clinicopathologic, IHC description 4 , 7 , 17 – 20 were included and summarized in Tables 2 – 4 . Clinical features of 77 LG-FLAC and 97 HG-FLAC cases from the published studies and the current study were analyzed (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…After a careful review, 12 articles with featured molecular findings 4 , 7 9 , 18 , 22 25 and/or detailed clinicopathologic, IHC description 4 , 7 , 17 – 20 were included and summarized in Tables 2 – 4 . Clinical features of 77 LG-FLAC and 97 HG-FLAC cases from the published studies and the current study were analyzed (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…25 In some studies, mutations in both DICER1 and CTNNB1 have been found in PB and L-FLAC. 26,27 In these two cases of PB, β-catenin was also mainly expressed in membrane and multifocal cytoplasmic/ nuclear localization. These cases further support the genetic abnormalities shared by L-FLAC and PB, and the mutation of DICER1 may be related to the abnormal expression…”
Section: Discussionmentioning
confidence: 89%
“…Both L‐FLAC and PB are closely related to CTNNB1 gene mutation 25 . In some studies, mutations in both DICER1 and CTNNB1 have been found in PB and L‐FLAC 26,27 . In these two cases of PB, β‐catenin was also mainly expressed in membrane and multifocal cytoplasmic/nuclear localization.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the high prevalence of CTNNB1 mutation is a hallmark of L-FLAC and could serve as a diagnostic marker. Next generation sequencing for L-FLAC cases allowed the detection of DICER1 mutations [8, 10,11]. DICER1 encodes an RNase III family endoribonuclease that plays an essential role in microRNA production [16].…”
Section: Discussionmentioning
confidence: 99%